A Study of Environmental Awareness of High School Students: Exploring the Role of High School Education in Environmental Preservation and Improvement (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Environment refers to the sum total of condition andinfluence that affects the life and development of organism. The qualitativedevelopment and quantitative progress of mankind depends on the quality ofenvironment. Therefore, there are no two views about the fact that , it is theprimary responsibility of man not only to preserve the environment but also toimprove it qualitatively.